METODE DAN PROSEDUR PELAKSANAAN REKRUTMEN SELEKSI PT. BANK RAKYAT INDONESIA (PERSERO) Tbk - Ade Iqbal Prasetya; Ardian Dwi Cahyo; Atiqatul Maula (Universitas Trunojoyo Madura, 2018)
ABSTRACTThe purpose of this research is to explain about the method and procedure of rectification that has been used by BRI Tanjung Bumi Branch Unit. To provide an explanation of the understanding and characteristics of qualified employees according to the BRI Bumi Tanjung Branch Unit. The method used in this research is qualitative descriptive. With data collection techniques using interviews and documentation. The results of the study show that the Tanjung Bumi Branch BRI Unit uses internal and external recruitment methods using newspaper and internet media, with online registration for registration, recruitment procedures starting from field reports needed by employees, then to the directors, and human resources. There are two selection methods, namely administration selection method and management selection method, the selection procedure starts from the selection procedure of the Tanjung Bumi Branch BRI Unit starting from theoretical tests, practice tests, academic interviews, aptitude tests, directors interview tests, and finally health tests. Qualified employees are employees who are able to carry out tasks that are given and have skills, and are characterized by discipline, creative loyalty, working optimally, and having expertise.